SCHOOL PRINCIPAL LEADERSHIP STRATEGIES IN IMPROVING THE QUALITY OF ISLAMIC EDUCATION - Abidin, Zainal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore and analyze effective leadership strategies of school principals in improving the quality of Islamic education in schools. Quality leadership is the key in facing various challenges and dynamics in the education system. The main focus of this research is to identify leadership practices that are successfully implemented by school principals to improve the quality of Islamic education. The research method used is a qualitative approach by collecting data through in-depth interviews with several school principals who are considered successful in improving the quality of Islamic education in their institutions. Data analysis was carried out using a thematic approach to identify general patterns in the leadership strategies implemented. The research results show that an effective school principal leadership strategy involves active involvement in developing the school's vision and mission, empowering teaching staff, implementing innovative learning models, as well as synergistic efforts with local stakeholders and the community. School principals who are able to build an inclusive work culture and provide ongoing support to staff and students are likely to achieve significant improvements in the quality of Islamic education.